PENGAWASAN PEKERJAAN KONSTRUKSI OLEH PEJABAT PEMBUAT KOMITMEN TERHADAP PENYEDIA JASA KONSTRUKSI DI KABUPATEN MELAWI - Redin - (Universitas Kapuas Sintang, 2021)
This study was conducted with the aim of knowing and analyzing how the supervision of construction work by Commitment Making Officials towards bridge construction service providers and what factors were an obstacle for CMO to supervise construction service providers in the construction work of the Imat river bridge construction in Melawi Regency. By using normative juridical research methods, it can be concluded that first, CMO has carried out supervision, but it is not optimal because the construction of the Imat river bridge was completed beyond the specified time or not on time as stated in the contract and SPMK. For delays, construction service providers are subject to a late fine of 1/1000 (one per thousand) of 777,337,000, and payment delays are made until the work is completed. Second, for the convenience of CMO in carrying out supervision at the planning stage, a Letter of Agreement/Contract, SPMK (order to start work) and work planning related to ordinary embankment and stone installation on the Imat river bridge have been made which are used as guidelines for supervision of work. However, there are internal and external factors that hinder the implementation of supervision as planned. Internal factors are the limited number of supervisors and quite a number of construction projects/works that must be supervised by supervisors in 2019. Meanwhile, external factors are the condition of damaged roads as accessibility to the monitoring location, and project/construction work locations that are far from the PUPR office.Keywords: Supervision, Construction Service Users, Construction Service Providers.